Implementation of 3D Animation Video-Based Learning Media in the Introduction of Silat Martial Arts in the Brotherhood of Setia Hati Terate (PSHT) - Sahputra, Rifaldi Arridho; Marbun, Nasib (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Persaudaraan Setia Hati Terate (PSHT) is one of the organizations that has an important role in the development and preservation of martial arts in Indonesia. Saifullah An-Nahdliyah Islamic Boarding School is one of the educational institutions that organizes the teaching of martial arts of the Persaudaraan Setia Hati Terate (PSHT). However, in the learning process applied to the introduction of martial arts Silat Persaudaraan Setia Hati Terate at Saifullah An-Nahdliyah Islamic Boarding School, there are still problems that can affect the effectiveness of Silat martial arts learning for students, namely the unavailability of learning media that supports other than direct training at Saifullah An-Nahdliyah Islamic Boarding School. This study aims to implement 3D animation video-based learning media in the introduction of martial arts of the Setia Hati Terate Brotherhood at Saifullah An-Nahdliyah Islamic Boarding School. The data collection techniques used to obtain the research data needed in this study are observation techniques, interviews, documentation, and literature studies. 3D animation video for learning media introduction to martial arts Pencak Silat Persaudaraan Setia Hati Terate at Saifullah An-Nahdliyah Islamic Boarding School is made using Blender application. The concept of 3D animation video made in this research is to present the introduction of martial arts by making moving characters, which can be accessed offline.